Comparison of the Results of Modeling Pulmonary Fibrosis in Sprague Dawley Rats by Intratracheal Administration of Bleomycin in the Form of Sulfate and Chloride at a Dose of 3 mg/kg - Elena A. Tukhovskaya; Yulia A. Palikova; Mariya S. Severyukhina; Alina M. Ismailova; Victor A. Palikov; Gulsara A. Slashcheva; Natalya A. Borozdina; Evgeniy S. Mikhaylov; Irina N. Kravchenko; Vitaly A. Kazakov; Ekaterina N. Kazakova; Elena A. Kalabina; et al. (MDPI AG, 2024)
Background/Objectives: Intratracheal administration of bleomycin (BLM) to laboratory rodents is a standard, widely used technique used to model pulmonary fibrosis (PF). BLM, as a modeling agent, is produced mainly in the form of two salts-sulfate and chloride. We compared the results of modeling PF in SD rats by intratracheal administration of BLM sulfate and BLM chloride. Methods: Healthy mature male SD rats were used. PF was modeled by intratracheal administration of BLM sulfate and BLM chloride at a dose of 3 mg/kg. The criteria for the development of PF included body weight gain, changes in respiratory parameters, relative lung weight, cellular composition of broncho-alveolar fluid (BALF), histological assessment of the severity of PF with trichrome Masson staining. Results: Intratracheal administration of both BLM salts led to the development of pronounced PF, which was determined by changes in all of the measured parameters relative to control animals. There were no significant differences between the BLM sulfate and BLM chloride groups in body weight gain, hydroxyproline content, and histological evaluation. However, significant differences were identified in the cellular composition of BALF-a significant increase in alveolar macrophages and neutrophils levels in animals treated with BLM sulfate. Conclusions: Intratracheal administration of both BLM salts led to the development of severe PF; however, the inflammatory process in animals receiving BLM sulfate was more pronounced and prolonged than in animals receiving BLM chloride, which in the former, when observed more than 21 days after modeling, can lead to more severe PF.